已知P(B)=0.5,P(B-A)=0.1,则P(AB)= ( )
A: 0
B: 0.1
C: 0.4
D: 0.6
A: 0
B: 0.1
C: 0.4
D: 0.6
C
举一反三
- 已知P(A)=0.4,P(B)=0.3,P(AB)=0.2,, 则以下结果正确的是 A: P(B∣A)=0.5 B: P(B-A)=0.1 C: P(A-B)=0.1 D: P(B∣A)=0.75 E: P(B-A)=0.3 F: P(B∣A)=1
- 已知A,B为互斥事件,且P(A)=0.4,P(B)=0.2,P(AB=0.1),则P(A∪B)=() A: 0.4 B: 0.5 C: 0.6 D: 0.7
- 已知P(AB)=0.1, P(A)=0.5,则P(B|A)= ( ) A: 0.08 B: 0.2 C: 0.5 D: 0.6
- 已知随机事件A,B,P(A) =0.3,P(B) =0.4,P(AB)=0.2,则P(AB)=()。 A: 0.1 B: 0.2 C: 0.4 D: 0.5
- 已知P(A)=0.5,P(B|A)=0.2,则P(AB)= ( ) A: 0.4 B: 2.5 C: 0.01 D: 0.1
内容
- 0
设P(A)=0.5,P(B|A)=0.6,P(B-A)=0.1,求P(B),
- 1
已知P() = 0.3,P() = 0.2,P(A|B)=0.5,P()=( ). A: 0.4 B: 0.15 C: 0.6 D: 0.1
- 2
若P(A)=0.5,P(B)=0.4,P(A-B)=0.3,则P(AB)=() A: 0.1 B: 0.2 C: 0.5 D: 0.4
- 3
设P(A)=0.5,P(B)=0.3,P(AB)=0.6,则P(AB)=()。 A: 0.1 B: 0.2 C: 0.3 D: 0.5
- 4
已知事件A与B相互独立,P(B)=0.2,P(A-B)=0.4,则P(B-A)= A: 0.5 B: 0.3 C: 0.2 D: 0.1